COMPARISON OF THE PARENTERAL AND ORAL VITAMIN D SUPPLEMENTATION IN THE TREATMENT OF NUTRITIONAL RICKETS IN TERMS OF MEAN CHANGE IN SERUM CALCIUM, PHOSPHORUS, AND ALKALINE PHOSPHATASE - Sumaira Tehseen; Tahir Mehmood; Nisar Khan Sajid; Tanveer Ahmed; Ramsha Abbas; Saeed Ahmed (Journal of University Medical & Dental College, 2021)
ABSTRACT: BACKGROUND & OBJECTIVE: Rickets is a common presentation on the pediatric floor, with nutritional rickets being the cause of leading significant morbidity, disability, especially in the developing countries of the world. The objective is to compare the efficacy of parenteral and oral vitamin D supplementation in the treatment of nutritional rickets METHODOLOGY: This comparative interventional, prospective analysis was conducted at Aziz Fatimah Hospital Faisalabad (1-1-2017 to 30-6-2017) outdoor patients divided into parenteral and oral groups. All of the outcome variables were measured at baseline and one month after treatment.RESULTS: In this study, mean age was calculated as 2.12 + 0.76 years and 2.15+0.77 in parental and oral groups respectively. 49.29% (n=69) and 45%(n=63) were male and 50.71%(n=71) and 55% (n=77) were female respectively in both groups.  At baseline, serum calcium was 8.68 + 0.35 and 8.71 + 0.37 (p=0.62) serum phosphorus was 3.92 + 9.22 and 3.84 + 0.20 (p=0.03), and serum alkaline phosphatase was 230.01 + 13.09 and 228.89 + 13.80 (p=0.48) in parenteral and oral groups respectively. After treatment the mean change seen in serum calcium was 1.14 + 0.26 and 0.72 + 0.19 (p=0.001), serum phosphorus was 1.42 + 0.33 and 0.71 + 0.26 (p=0.001), serum Alkaline phosphatase was 79.48 + 14.84 and 23.65 + 12.21 (p=0.001) in parenteral and oral groups respectively.CONCLUSION:  We concluded that the parenteral route for vitamin. D supplementation is significantly better than the oral route in treating nutritional rickets in terms of mean change in serum calcium, serum phosphorus, and serum alkaline phosphatase.